Leader Humility and Employees’ Accountability During The Pandemic - Septiandari, Aditya; Riantoputra, Corina D.; Samian (Universitas Prasetiya Mulya, 2021)
One way of achieving work effectivity is by making sure employees show accountability. Accountability is becoming even more important during the pandemic, where organizations are forced make their employees work from home. This study aims to identify the process of how leaders and organizations can shape accountability. This research argues that leader humility may enhance employee’s perceived organizational support which eventually shaped employee’s accountability. This study was conducted toward 145 employees from a stateowned company in Jabodebek area via an online survey. This study finds (1) leader humility positively affect employee’s accountability; (2) leader humility positively affects perceived organizational support; (3) perceived organizational support positively affect employee’s accountability; (4) perceived organizational support significantly mediated the relationship between leader humility and accountability. The mediation model predicts 27% of accountability’s variance and is able to provide contribution to accountability’s studies that leader and organizational aspects are essentials in affecting accountability.